Study Role of Creatinine, Triglycerides, Urea, Cholesterol, Sugar in Patients with Diabetes Mellitus Type 1 - Dawood, Muhammad Firas; Mohammed, Abdul Hadi Abbas; Katie, Zainab Abdul Rahman; hamed hasan, Bent Al-huda; Abdullah, Dr. Jassim Abdel Abbas (Journal of Science in Medicine and Life, 2024)
Background: Diabetes is a chronic disease caused by the pancreas producing insufficient insulin or the body utilizing insulin inefficiently. Diabetes comes in three primary forms: Diabetes type 1 diabetes type 2 pregnancy diabetes Diabetes type 1, Often called insulin-dependent diabetes, this chronic condition results in complete lack of insulin production by the pancreas. The hormone insulin is necessary for sugar, or glucose, to enter cells and start the process of producing energy. When the body is unable to utilise insulin efficiently or create enough of it, type 2 diabetes, a complicated chronic illness, develops. People with type 2 diabetes need therapy in order to keep their blood sugar and insulin levels under control. Materials and methods: The results of the analyzes data were collected (Hba1c, T.G., sugar, cholestrol, urea, creatinine). From the following hospitals: Imam Hussain Medical Learning City (Holy Karbala) Marjan Medical Educational City (Babylon) Children's Teaching Hospital (Babylon) Al-Moussawi National Hospital (Basra) For the purpose of studying the effect of Hba1c on: urea cholesteol creatinine triglyceride sugar Results and Conclusion Results The results of our research showed that there is a significant relationship with sugar and there is no relationship with the rest Conclusion Diabetes is affected by the level of sugar in the blood, which in turn affects the values of Hba1c, and there must be periodic examination of diabetics to avoid side.